Pengaruh Faktor Fundamental Terhadap Harga Saham Industri Perbankan : Studi Pada Bursa Efek Indonesia - Siti Hardiyanti; Lukman Chalid; Muh Syafi’i Basalamah (CV ODIS, 2022)
This research aims to find out the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), Price Earnings Ratio (PER), Earning Per Share (EPS) and Price to Book Value (PBV) on the stock prices of the banking industry listed on the Indonesia Stock Exchange. This research period was conducted for 5 (five) years, namely in 2015-2019. The type of data used in this study is quantitative data. The data source used is secondary data in the form of annual financial statements of banking companies from 2015-2019 obtained from the Indonesia Stock Exchange (www.idx.com) and the Stock Exchange Investment Gallery of the Faculty of Economics, Universitas Muslim Indonesia. The research population is all banking companies listed on the Indonesia Stock Exchange for the period 2015-2019, namely 43 banking companies. The samples obtained based on purposive sampling techniques were obtained by 23 companies. The data analysis model used to explain the effect of fundamental variables on stock prices is multiple linear regressions. Based on the results of the data analysis, the Variable Return on Equity (ROE) has a significant effect on the stock price with a significance value of 0.016. The Variable Debt to Equity Ratio (DER) has a significant effect on the stock price with a significance value of 0.001. The Variable Price Earnings Ratio (PER) had no significant effect on the stock price with a significance value of 0.534. Variable Earnings Per Share (EPS) has a significant effect on the stock price with a significance value of 0.004. Variable Price to Book Value (PBV) has a significant effect on the stock price with a significance value of 0.000.